Phytochemical study and isolation of secondary metabolites from Ziziphus mauritiana leaves - Daniel, Thierry Henry; Lahuri, Azizul Hakim; Sulaiman, Syazreen Nadia; Nordin, Norazzizi; Jaafar, Nur Farhana; Ramdhani, Eka Putra; Dzakaria, Norliza (IOP Publishing, 2025)
Ziziphus mauritiana is recognized as a medicinal plant with various therapeutic properties, including activity against chronic ailments such as cancer and diabetes, and possessing antioxidant effects. However, comprehensive phytochemical screening and isolation of secondary metabolites across the full range of crude extract polarities (non-polar, semi-polar, and polar) present a significant methodological challenge. This study directly addresses this gap by establishing a systematic extraction and isolation methodology. This work aims to isolate and determine the molecular structure of secondary metabolites from the leaves of Z. mauritiana . The study used sequential cold maceration extraction with solvents of ascending polarity, hexane (non-polar), ethyl acetate (semi-polar), and ethanol (polar) followed by separation using thin layer chromatography (TLC) and column chromatography (CC). Molecular structures were determined using Nuclear Magnetic Resonance ( 1 H NMR) spectroscopy and confirmed with literature data. The extraction yielded a total of 2.661 g of crude extracts, with the highest yield from the non-polar hexane fraction. Four compounds were successfully isolated and structurally elucidated for geranylacetone (0.16 g) and linoleic acid (0.163 g) from the non-polar crude, and 6,10,14-trimethylpentadecan-2-one (0.214 g) and heptadecane (0.410 g) from the polar crude. These isolated secondary metabolites are consistent with the qualitative phytochemical screening and are known to possess antimicrobial, therapeutic, and antitoxicity properties. This study contributes established, quantified extraction and isolation methodologies for Z. mauritiana leaves, providing a valuable chemical profile for future applications in medicine, agriculture, and cosmetic formulations.